Antimicrobial efficacy of composite irrigation solution against dominant pathogens in seawater immersion wound and in vivo wound healing assessment - Wang, Xin; Tan, Jie; Ni, Shenpeng; Zhou, Dengyun; Liu, Baolin; Fu, Qiang (Frontiers in Microbiology, 2023)
Seawater immersion wound is inevitably accompanied by bacterial infection. Effective irrigation is critical for bacterial infection prevention and wound healing. In this study, the antimicrobial efficacy of a designed composite irrigation solution against several dominant pathogens in seawater immersion wound was evaluated, and in vivo wound healing assessment was conducted in a rat model. According to the time-kill result, the composite irrigation solution exhibit excellent and rapid bactericidal effect against V. alginolyticus and V. parahaemolyticus within 30s of treatment, while eliminate C. albicans, P. aeruginosa, E. coli and the mixed microbes after 1 h, 2 h, 6 h and 12 h of treatment, respectively. And significant bacterial counts reduction of S. aureus was observed after 5 h treatment. Besides its skin non-irritating attribute, the in vivo wound healing results further demonstrated that the irrigation solution showed high repair efficiency in skin defect model inoculated with the mixed microbes. The wound healing rate was significantly higher than that of the control and normal saline groups. It could also effectively reduce the number of viable bacteria on the wound surface. The histological staining indicated that the irrigation solution could reduce inflammatory cells, promote collagen fibers and angiogenesis, thereby promote wound healing. We believed that the designed composite irrigation solution has great application potential in the seawater immersion wounds treatment.